PENGARUH TIPE KEPRIBADIAN DAN PERILAKU KONSUMTIF TERHADAP PERENCANAAN KEUANGAN PADA MAHASISWA DI SIDOARJO: THE INFLUENCE OF PERSONALITY TYPE AND CONSUMPTIVE BEHAVIOR ON FINANCIAL PLANNING AMONG STUDENTS IN SIDOARJO - Zuhdi, Muhammad Nadhim; Mustaqim, M (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This studies pursuits to decide the partial influence among personality type and consumer behavior on financial planning. This type of studies is quantitative descriptive. The studies objects are college students in Sidoarjo Regency. The population and sampleon this study aren't yet known, so the Lemeshow formula was used to obtain at least 90 respondents. Analysis Data used reliability tests, validity tests, normality test, Glejser heteroscedasticity tests, multicollinearity tests, multiple linear regression analysis and t tests with tools statistics for example IBM SPSS 24. The reseach result show that personality type affects financial planning among college students in Sidoarjo Regency, but consumer behavior does no longer affects financial planning among college students in Sidoarjo Regency.